2020
DOI: 10.3390/diagnostics10100789
|View full text |Cite
|
Sign up to set email alerts
|

Tear Film Osmolarity Measurement in Japanese Dry Eye Patients Using a Handheld Osmolarity System

Abstract: We studied the efficacy and safety of a handheld osmolarity measurement system (I-PEN) in Japanese patients with dry eye disease (DED) and non-DED subjects. In this prospective, multicenter study, tear osmolarity was examined using the I-PEN in a total of 122 eyes divided into DED (n = 71) and non-DED (n = 51) groups. Subjective symptoms were assessed using the Dry Eye-Related Quality-of-Life Score (DEQS) questionnaire. Ocular surface condition was evaluated in terms of fluorescein tear breakup time (FBUT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, just one research has ever reported the tear osmolarity measured by I-Pen in DED patients. Shimazaki et al, adopted the I-Pen osmometer in Japanese DED patients and reported its clinical utility 28 . In the study, symptomatic eyes with TBUT ≤ 5 s, were regarded as having DED, and noneligible subjects were defined as normal control, irrespective of Schirmer test or ocular surface staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, just one research has ever reported the tear osmolarity measured by I-Pen in DED patients. Shimazaki et al, adopted the I-Pen osmometer in Japanese DED patients and reported its clinical utility 28 . In the study, symptomatic eyes with TBUT ≤ 5 s, were regarded as having DED, and noneligible subjects were defined as normal control, irrespective of Schirmer test or ocular surface staining.…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancy between our results and those of Shimazaki et al, can be explained by the different definition of DED and difference in prevalence of short TBUT-type DED. Also, as they admitted, operator error resulting in ocular irritation and lacrimation, leading to inaccuracy in measuring tear osmolarity is possible due to the multiple examiners in their multicenter study design 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Each subject is asked to close their eyelids gently for 30 s, and the disposable single-use sensor then softly makes contact with the palpebral conjunctiva from the lower eyelid at a 30° angle. By design, the I-PEN beeps after a few seconds and displays an osmolarity reading on the screen ( 78 , 79 ). Tear osmolarity is measured three times in the right eye of each subject with 5-min intervals between measurements.…”
Section: Tear Examinationmentioning
confidence: 99%
“…Shimazaki et al ( 78 ) studied the efficacy and safety of the handheld I-PEN in Japanese patients with dry eye disease and those without dry eye disease and found no correlations between the tear film osmolarity values obtained with the I-PEN system and any subjective or objective parameters of dry eye. Meanwhile, in the study of Fagehi et al ( 79 ), the mean measurement of I-PEN tear osmolarity was 303.8 ± 4.8 mOsm/L, which is in agreement with the range reported for healthy subjects.…”
Section: Tear Examinationmentioning
confidence: 99%
“…Thus, timely DED diagnostics can serve as a live-saving diagnostics marker in the elderly population. However, the osmolarity measurements are not lacking challenges [9] as (i) they suffer from significant inter-and intra-individual variability and (ii) require expensive equipment as the values obtained with hand-held device do not correlate with any subjective or objective parameters of DED. Another approach developed by Itokawa et al [10] probes the correlation between temperature and blood flow in the ocular anterior segment, and their effects on corneal temperature which is in turn related to the overall stability of the tear film.…”
mentioning
confidence: 99%